Bank Mergers and Crime: The Real and Social Effects of Credit Market Competition - Mark J. Garmaise
Using a unique sample of commercial loans and mergers between large banks, we provide microlevel (within-county) evidence linking credit conditions to economic development and find a spillover effect on crime. Neighborhoods that experienced more bank mergers are subjected to higher interest rates, diminished local construction, lower prices, an influx of poorer households, and higher property crime in subsequent years. The elasticity of property crime with respect to merger-induced banking concentration is 0.18. We show that these results are not likely due to reverse causation, and confirm the central findings using state branching deregulation to instrument for bank competition.